Does Etiology of Acute Pancreatitis Matter? A Review of 391 Consecutive Episodes - Weitz, Gunther; Woitalla, Julia; Wellhöner, Peter; Schmidt, Klaus; Büning, Jürgen; Fellermann, Klaus (JOP. Journal of the Pancreas, 2015)
Context Acute pancreatitis can be triggered by a variety of factors ranging from short lasting to sustained disruptions. It is plausible that the characteristics and course of disease differ among etiologies. Data distinguishing characteristics of patients with pancreatitis of biliary, alcoholic, idiopathic or other origin are scarce and conflicting. Objective To compare patients’ characteristics, baseline parameters on admission, and outcome in patients with an episode of acute pancreatitis in whom the etiology was thoroughly determined. Design Retrospective study. Setting Single center. Patients Three-hundreds and 91 consecutive episodes of acute pancreatitis through the years 2008 to 2011. Main outcome measures Gender, age, body mass index, Charlson comorbidity index, history of pancreatitis, heart rate, blood pressure, plasma lipase, hematocrit, plasma creatinine, white blood cell count, rate of persistent organ failure and necrosis, maximum C-reactive protein, duration of hospitalization, mortality. Results There were marked differences between the groups. Biliary etiology was associated with higher age and body weight, female predominance, higher plasma lipase, and a favourable outcome. Alcoholic etiology had male predominance, a tendency for initial hemoconcentration, a lower plasma lipase, and the highest rate of necrosis. Idiopathic etiology had the highest rate of persistent organ failure and the highest mortality. Conclusions Biliary, alcoholic and idiopathic acute pancreatitis should be treated as distinct entities. While alcoholic episodes have the highest risk of necrosis, the worst outcome was observed in the idiopathic group. Hence, finding no causality for an episode of acute pancreatitis after thorough investigation might be a predictor for poor outcome. Larger studies are warranted to confirm this. Image: Age and gender distribution of the episodes of acute pancreatitis sorted by etiology.